2017
DOI: 10.1177/1753193417709949
|View full text |Cite
|
Sign up to set email alerts
|

Early active motion after rigid internal fixation of unstable extra-articular fractures of the proximal phalanx

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 20 publications
0
25
0
2
Order By: Relevance
“…Firm fixation and early rehabilitation are recommended to prevent postoperative extensor tendon adhesions and ROM limitation [ 14 , 15 ], Miller et al. reported that functional recovery (ROM, pain relief, return to work, and grip strength) was mostly achieved within the first 6 postoperative weeks [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firm fixation and early rehabilitation are recommended to prevent postoperative extensor tendon adhesions and ROM limitation [ 14 , 15 ], Miller et al. reported that functional recovery (ROM, pain relief, return to work, and grip strength) was mostly achieved within the first 6 postoperative weeks [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,5,6,14 No obstante, para asegurarse de mantener o mejorar la movilidad preoperatoria, es esencial utilizar una osteosíntesis rígida que permita una rehabilitación activa temprana. [15][16][17] Entre las fortalezas de nuestro estudio, podemos enumerar el considerable tamaño de la serie teniendo en cuenta la esporádica frecuencia con que se realiza este procedimiento.…”
Section: Discussionunclassified
“…TAM measurement of the affected finger was made. TAM was calculated by subtracting the sum of distal IP (DIP), proximal IP (PIP) and MCP joint extensor lag from MCP, PIP and DIP joint flexion for the affected finger (Ataker et al., 2017). The DASH questionnaire was used for functional evaluation, and the VAS was used for pain evaluation.…”
Section: Methodsmentioning
confidence: 99%